Pemberdayaan Kader dan Tenaga Kesehatan Melalui Edukasi dan Pelatihan pada Kelas Menyusui di Wilayah Kerja Puskesmas Kota Palembang - Virgian, Kharisma; Setiawati, Desy; Regita, Althaf Ardhiea; Komariah, Nurul; Febiola, Fenny; Meilinda, Viny Reka (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
The coverage of exclusive breastfeeding both in the world and in Indonesia still shows low numbers. According to WHO data, the average exclusive breastfeeding globally is only 38%. The National Health Survey reported that the proportion of babies aged 6-23 months who received exclusive breastfeeding nationally was 55.5%. The coverage of exclusive breastfeeding in South Sumatra Province in 2023 is 70%, which has not reached the program target. According to data from the Palembang City Health Profile in 2023, the number of babies aged < 6 months who received Exclusive Breastfeeding reached 80.4%. The Coverage of Exclusive Breastfeeding in the Empat Ulu Palembang Health Center Working Area is still 48.3%. The goal is to make the work area of the Empat Ulu Palembang Health Center an area with Exclusive Breastfeeding coverage that has increased from previous years by mobilizing community groups, namely Posyandu Cadres and Health Workers, through education, training, and assistance about Breastfeeding Classes. So it is hoped that these cadres and trained health workers can accompany and nurture pregnant women in the third trimester about breastfeeding preparation and breastfeeding mothers who have babies 0-6 months so that they can breastfeed properly and correctly and can provide Exclusive Breastfeeding properly. And can increase the knowledge and skills of mothers in giving breast milk to their babies.